PERFORATED JEJUNAL DIVERTICULITIS AS AN UNCOMMON CULPRIT OF ACUTE ABDOMEN: A CASE REPORT AND REVIEW OF LITERATURE - Maqbool, Umar; Mehmood, Muhammad Fayzan; Maqbool, Abdullah; Qadeer, Ahsan; Loon, Muaz; Masood, Saad (Journal of Ayub Medical College Abbottabad, 2024)
Small intestinal diverticula are rare compared to colonic diverticula. Jejunal diverticulosis can occur in older men. These diverticula are usually asymptomatic but can present with acute abdomen when symptomatic. Complicated cases can present with perforation, peritonitis, and abscess formation. CT scan is the ideal imaging modality to diagnose perforated jejunal diverticulitis. Complicated cases warrant surgical intervention. A high clinical suspicion is necessary for the timely diagnosis of perforated diverticulitis. We are presenting a case of a 45-year-old who presented with an acute abdomen in a surgical emergency. Perforated jejunal diverticulitis was revealed as the cause of his symptoms during surgery. This case signifies the importance of varied clinical presentations of perforated jejunal diverticulitis and keeping it in the differentials of acute abdomen. Perforated diverticulitis has a high mortality rate, so timely management is of utmost importance.